Hubungan Dow Jones Islamic Market Index Malaysia, Jepang, China dengan Jakarta Islamic Index Menggunakan Analisis Vector Error Correction Model - Andi Nurhidayati; Syariati, Alim; Rusnawati (Study of Scientific and Behavioral Management, 2024)
The development of the Sharia capital market in Indonesia cannot be separated from the influence of foreign capital markets, especially in the Asian region. The fluctuations in the Jakarta Islamic Index (JII) indicate a contagion effect from the stock price movements of other countries. This study focuses on the relationship between the Dow Jones Islamic Market Index (DJIMI) in Malaysia, Japan, and China with JII. This study employs Vector Error Correction Model (VECM) analysis using monthly stock price index data from each variable from January 2021 to December 2023. In the long term, DJIMI Japan has a significant positive relationship with JII, DJIMI China has a significant negative relationship, while DJIMI Malaysia has no significant relationship. In the short term, DJIMI Malaysia, DJIMI Japan, and DJIMI China have no significant relationship with JII. This study is limited to the relationship between variables through the stock price index. Future studies need to include factors such as inflation, exchange rates, BI rate, and world gold prices in relation to market integration. This study uses contagion effect theory, market integration, and investment portfolio diversification to explain the relationships between the indices.